Nab-paclitaxel/gemcitabine first line therapy in patients with metastatic pancreatic carcinoma and high-bilirubin values: data from the German QoliXane pancreatic cancer registry - Hausen, Gerrit zur; Springfeld, Christoph; Härtel, Nicolai; Hofheinz, Ralf-Dieter (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: Hyperbilirubinaemia is a common disease effect in patients (pts) with metastatic pancreatic cancer (mPC). As clinical trials often exclude them, data on management of these pts are rare. In the framework of a German observational multicenter study (QoliXane), quality of life and therapy data are currently being collected in pts with mPC receiving a combination of nab-paclitaxel and gemcitabine. This is an interim analysis on hyperbilirubinaemia management.Methods: Pts were included to this analysis if they entered the trial with a bilirubin level ≥ 1.2 mg/dl and completed at least 2 cycles. Bilirubin levels were documented for up to 4 cycles and methods of hyperbilirubinaemia management have been assessed. A both descriptive and explorative analysis was performed using IBM SPSS V 23.Results:...